Potential anti-COVID-19 agents, cepharanthine and nelfinavir, and their usage for combination treatment - Ohashi, Hirofumi; Watashi, Koichi; Saso, Wakana; Shionoya, Kaho; Iwanami, Shoya; Hirokawa, Takatsugu; Shirai, Tsuyoshi; Kanaya, Shigehiko; Ito, Yusuke; Kim, Kwang Su; Nomura, Takao; Suzuki, Tateki; et al. (iScience, 2021)
Antiviral treatments targeting the coronavirus disease 2019 are urgently required. We screened a panel of already approved drugs in a cell culture model of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and identified two new agents having higher antiviral potentials than the drug candidates such as remdesivir and chroloquine in VeroE6/TMPRSS2 cells: the anti-inflammatory drug cepharanthine and human immunodeficiency virus protease inhibitor nelfinavir. Cepharanthine inhibited SARS-CoV-2 entry through the blocking of viral binding to target cells, while nelfinavir suppressed viral replication partly by protease inhibition. Consistent with their different modes of action, synergistic effect of this combined treatment to limit SARS-CoV-2 proliferation was highlighted. Mathematical modeling in vitro antiviral activity coupled with the calculated total drug concentrations in the lung predicts that nelfinavir will shorten the period until viral clearance by 4.9 days and the combining cepharanthine/nelfinavir enhanced their predicted efficacy. These results warrant further evaluation of the potential anti-SARS-CoV-2 activity of cepharanthine and nelfinavir. [Display omitted] •Nelfinavir (NFV) inhibits SARS-CoV-2 replication•Cepharanthine (CEP) inhibits SARS-CoV-2 attachment to target cells•Combination of NFV and CEP can synergistically augment antiviral activity•NFV and CEP are estimated to shorten the time to viral elimination at clinical doses Medical Substance; Pharmaceutical Preparation; Virology;